(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
This case report describes the orthodontic treatment of an adult patient, who presented an Angle Class II division 2 malocclusion, with deep traumatic overbite, retroclined incisors with proclined left maxillary lateral incisor and mild gingival recessions. Treatment of an adult Class II patient requires careful diagnosis and a treatment plan involving esthetic, occlusal, and functional considerations. The patient was treated with extraction of four first premolars to relieve crowding, with simultaneous correction of the deep bite by intrusion of the upper and/or lower incisors using fixed appliance mechanotherapy. Ban J Orthod & Dentofac Orthop, April 2013; Vol-3, No.2